Initial Days of Revised Basic Course Workshop in Medical Education in India: An End-training Analysis - Joshi, Urvish K; Vyas, Sheetal (National Journal of Community Medicine, 2016)
Introduction: Indian Medical-education is undergoing transformation. Faculty-development workshop is revised across nation. One of the first such batches was assessed. Methodology: All 26 participants of rBCW from various departments and of different cadres from tertiary-care-teaching-hospital filled up end-training-questionnaire about their general perceptions, course-content and recommendations. Paired t-test and percentages were calculated. Results: 73.1% faculties were assistant professors or seniors, mean age being 35.5 years. Everyone had experience of undergraduate teaching with varying degree of exposure to MET. Significant increase in motivational level and confidence was seen. Awareness was lowest about competency-based teaching. Affective domain was neglected. Only 23% participants put in some thought behind their academic work. Majority agreed on personal utility of workshop. 84.6% wanted IMG to be only a clinician. Introduction of students’ feedback, assessment pattern change, were widely suggested areas. Perceived academic challenges and solutions were mainly human resource, infrastructure and workload. Discussion: Changes in curriculum and consistent emphasis on affective domain and competency-based-education needed. Hand-holding of young faculties, feedback from students and parents, changes in students’ assessment pattern are need of hour. IMG roles need to be disseminated amongst faculties clearly. Provision of conducive atmosphere for faculties and assessment-based-employment - are the way forward.